The periodical press in the post-war Slovene emigrant community in Argentina - Horvat, Avgust (Two Homelands, 2000)
Following their arrival in Argentina post-war Slovene emigrants continued their publishing activities just as they had in the refugee camps of Austria and Italy. They set themselves lofty goals. The numerous periodicals published by the emigrants are a constituentpart of their successful efforts to create in a foreign country a part of that homeland of which they had been deprived and to communicate their national values to subsequent generations. Although the community was not wealthy, its publishing activities, like all other areas of public life, were entirely financed from its own resources. Despite its great enthusiasm, however, the community was not able to sustain such a number of publications either in the financial sense or with the necessary number of intellectual contributions. More than fifty years later the second and third generations have not abandoned the publication of Slovene periodicals but are trying to preserve Slovene heritage in this field, in as far as they are still able to resist the process of assimilation.